Pengaruh keteladanan Umar Bin Khattab terhadap motivasi belajar siswa - Azzahra, Syifa; Nawawi, Kholil (Program Studi Magister Pendidikan Agama Islam, 2025)
This study aims to determine the influence of Umar bin Khattab’s exemplary character on students’ learning motivation in grade X of MAN 2 Kota Bogor. The study uses a quantitative approach with an explanatory method. Data were collected using questionnaires distributed to 64 students as research samples. The data were analyzed using simple linear regression with the help of SPSS version 27. The results showed a significant influence between Umar bin Khattab's exemplary character and students' learning motivation, with a significance value of 0.000 (<0.05) and a determination coefficient (R²) of 0.469. This indicates that Umar bin Khattab’s values contribute 46.9% to students’ learning motivation. This research emphasizes the importance of exemplary figures in education, particularly in the subject of Islamic Cultural History (SKI), to enhance students’ learning spirit and character. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh keteladanan Umar bin Khattab terhadap motivasi belajar siswa kelas X di MAN 2 Kota Bogor. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksplanatori. Data dikumpulkan melalui angket yang disebarkan kepada 64 siswa sebagai sampel penelitian. Analisis data dilakukan menggunakan regresi linier sederhana dengan bantuan SPSS versi 27. Hasil penelitian menunjukkan adanya pengaruh yang signifikan antara keteladanan Umar bin Khattab terhadap motivasi belajar siswa, dengan nilai signifikansi sebesar 0,000 (<0,05) dan koefisien determinasi sebesar 0,469. Artinya, keteladanan Umar bin Khattab menyumbang 46,9% terhadap motivasi belajar siswa. Penelitian ini menekankan pentingnya integrasi tokoh teladan dalam pendidikan Islam untuk membentuk karakter dan semangat belajar siswa.